Leg length inequality and its relationship with injuries incidence of young basketball players: an observational study. - Santos, Lucas Villalta; Rossi, Mateus Francisco; Oliveira, Claudia Santos; Neto, Hugo Pasin (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The leg length inequality (LLI) creates postural changes collaborating with the emergence of functional limitations and musculoskeletal disorders. In a sport like basketball inequality of the lower limbs may be added to the demands of the sport and generate an increase in the incidence of injuries. Objective: The aim of this study was to identify young basketball players from with structural or functional LLI and its influence in injury incidence in a period of 6 months. Methods: 18 players were followed with an average age of 14.50 ± 1.86 of a basketball team from the city of Sorocaba for a period of 6 months. At the beginning and end of that period were applied tests from the Morbidity Survey Report modified for basketball to obtain data such as physical characteristics, training time, incidence of injuries, quantitative and qualitative measurement of the length of the lower limbs. Results: 72.2% of players had LLI and 50% had some kind of injury during this period, among the most common, sprains and muscle strains. Conclusions: There was a high rate of players with LLI and a positive relationship between this inequality with the incidence of injury.